O microcrédito como um instrumento de política pública de combate à pobreza: o Empreender JP - Farias, Wanderleya dos Santos (2012)
Our study aims to examine the intentions and perspectives from which has been effected the microcredit program in João Pessoa city - Empreender JP. We aimed to examine the development of the program in its constitutive dynamics and profile of the public benefit and managers, as well as their history of involvement with the program. Some municipal public policies in Brazil have been embracing the idea that entrepreneurship small business associated with the microfinance can be an important strategy for overcoming poverty. This new breed of public policy that is trying to build a dialogue between disinsertions and microcredit raises debates, since the provision of funding programs for the poorer classes could be helping to spread a culture of self-employment that misalignment of the concept of wage and universal rights. On the other hand, it is possible that local managements that have a greater harmony with the construction of new and sociability are more open to popular participation may be articulating access to credit to strengthen the associative practices and community work. To understand how the city of João Pessoa articulated the connection between the micro and the disadvantaged sections of the local population, we traverse a path analytical, departure, was a central tenet of the interactions between state and civil society in the face of this social issue. The main methodological pillars that served as support for our study were the bibliographical and documentary research, participant observation and field research. We conducted semi-structured interviews with representatives of the technical-functional program and people who had access to microcredit. We visited small agricultural enterprises in rural Joao Pessoa and also attended a course in basic business management offered by this local policy. The survey results could give us some insights. One was that the microcredit program of the city of João Pessoa constitutes a public action against poverty where the notion of entrepreneurship is placed as a gateway to employability and the granting of small loans is seen as the institutional representatives an instrument that contributes to strengthening the individual capacities of the poor. We realize that institutional managers relied on the discourse of the public attended that could reach the release phase of credit passed through a filter of natural selection along the steps of Empreender JP the fact that many subscribers did not own abilities to cope with the the business world. We capture, too, that the notions of social vulnerability, simulation games business and human capital guided the ideological conception of the local program. In turn, we observed that local public policy has evolved in a field of tensions and challenges, as the farmers who obtained credit in Empreender JP experienced situations that were very different trajectories of the individuals who have applied the small business financing in urban.